APPLICATION OF MAGIC BALL-BASED GROUP INVESTIGATION MODELS TO IMPROVE COLLABORATIVE SKILLS AND STUDENT LEARNING MATHEMATICS RESULTS - Rusmidah Rusmidah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This research is motivated by teacher-centered learning that caused the lack of student activity in solving problems and finding answers together. This research aims to improve mathematical collaborative skills and student learning outcomes through the application of a magic ball-assisted group investigation learning model. The subject of the research was a classroom action research study on third grade students at SDN 008 Talang Perigi. The instrument used was the observation sheet and learning outcomes test. The results showed in the first cycle of collaborative mathematical skills students obtained an average of 55.77% with a high category and in the second cycle increased to 73.44% with a very high category. Student learning outcomes in the first cycle had an average of 67.83 with a percentage of classical completeness of 53%, increasing in the second cycle to 75.67 with a percentage of classical completeness of 83%. Based on the findings, it can be concluded that the application of the learning model of investigation ball assisted by magic ball can improve the collaborative skills of mathematics and learning outcomes of third grade students of SDN 008 Talang Perigi.